Determinants of Abortion in the Tehran Metropolis Based on the Lived Experiences of Tehranian Women - Ghazanfari , Razieh Sadat; Moini, Seyyed Reza; Pezhhan , Ali (Health Nexus, 2026)
This study was conducted with the aim of examining abortion in the Tehran metropolitan area using a grounded theory methodology. Purposeful and snowball sampling methods were employed, and semi-structured interviews were conducted with 33 women residing in Tehran who had undergone at least one induced abortion in a medical office under the supervision of a specialist physician between 2021 and 2025. Data analysis based on Strauss and Corbin’s interpretive analytical approach revealed three distinct pregnancy patterns among participants. In the first group, the main categories included alcohol and drug use and engagement in high-risk sexual relationships (causal conditions); dysfunction of the family institution and delegitimization of traditional lifeworld norms (contextual conditions); social control over women’s bodies and fertility and incompatibility of lifestyles (intervening conditions); the feasibility of safe abortion and the normalization or moral neutralization of abortion (interactional strategies); and physical and psychological consequences (outcomes). The core category was identified as “reproductive autonomy in the absence of socially legitimate relationships.” In the second group, the principal categories included the existence of extramarital relationships (causal condition); marital dysfunction, long-term suppression of sexual and emotional needs, husbands’ extramarital relationships, and perceived positive functions of extramarital relationships (contextual conditions); barriers to divorce (intervening condition); interaction with peer social networks, transformation of women’s attitudinal and behavioral systems, and resistance to traditional and religious socialization (interactional strategies); and physical and psychological consequences (outcomes). The core category was “redefinition of feminine roles in response to marital and social constraints.” In the third group, the main categories consisted of convergence toward discourses of voluntary childlessness or low fertility (causal condition); hardships of childbearing, economic difficulties, women’s employment, and respondents’ idealistic expectations regarding childrearing (contextual conditions); non-supportive social environments, marital life circumstances, and women’s social networks (intervening conditions); changes in fertility behavior and transformations in women’s attitudes toward childbearing (interactional strategies); and physical and psychological consequences (outcomes). The core category was “rationalization of fertility within the framework of modern life.”